2015
DOI: 10.2337/diaspect.28.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Meaning of Insulin Pump Use in Emerging Adults With Type 1 Diabetes

Abstract: Objective. The purpose of this study is to investigate the meaning of living with an insulin pump for the management of type 1 diabetes during the period of emerging adulthood. Through a phenomenological narrative, this study contributes to the reflective understanding of the everyday life experiences of this population.Methods. A hermeneutic phenomenological design was used for this study of nine emerging adults (aged 19–24 years). Data were generated through face-to-face interviews and analyzed using the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…This initial expectation (and potential contradiction) was seen as important to address by all parties (users/parents/HCPs) and perceptions of what the pump could do shaped subsequent expectations of the amount and nature of work required to master living with this new device . Reasons given by people with T1D for wanting to move to CSII from MDI included pursuit of greater stability and control over blood sugar levels, and desire for a more flexible lifestyle . Most users indicated that the new equipment made self‐management easier in terms of work required to balance glucose levels, enabling them greater flexibility in, for example; when/where/how they chose to eat; and undertaking spontaneous activities …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This initial expectation (and potential contradiction) was seen as important to address by all parties (users/parents/HCPs) and perceptions of what the pump could do shaped subsequent expectations of the amount and nature of work required to master living with this new device . Reasons given by people with T1D for wanting to move to CSII from MDI included pursuit of greater stability and control over blood sugar levels, and desire for a more flexible lifestyle . Most users indicated that the new equipment made self‐management easier in terms of work required to balance glucose levels, enabling them greater flexibility in, for example; when/where/how they chose to eat; and undertaking spontaneous activities …”
Section: Resultsmentioning
confidence: 99%
“…However, improved self‐management and “flexibility” sat in tension with increased expectations to learn new “work”; new skills and adopt new practices associated with a more complex piece of technology . Parents reported “putting their life on hold” while integrating the new tool into management of their child's diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations